A miniature 7g jumping robot - Kovac, M.; Fuchs, M.; Guignard, A.; Zufferey, J.-C.; Floreano, D. (2008 IEEE International Conference on Robotics and Automation, 2008)
Jumping can be a very efficient mode of locomotion for small robots to overcome large obstacles and travel in natural, rough terrain. In this paper we present the development and characterization of a novel 5 cm, 7g jumping robot. It can jump obstacles more than 27 times its own size and outperforms existing jumping robots by one order of magnitude with respect to jump height per weight and jump height per size. It employs elastic elements in a four bar linkage leg system to allow for very powerful jumps and adjustment of the jumping force, take-off angle and force profile during the acceleration phase.